Tension-compression asymmetry and shear strength of titanium alloys. (December 2021) - Suryawanshi, J.; Singh, Gaurav; Msolli, S.; Jhon, Mark H.; Ramamurty, U.
Abstract: The relation between the tension-compression asymmetry (TCA) and shear strength in a wide variety of Ti alloys was examined. For this purpose, uniaxial tensile and compression, and double shear strength tests were performed on 13 Ti alloys, which have different microstructural phases (α, α+β, and β) and underwent different thermo-mechanical histories. Results show that the tensile-to-compressive yield strength and shear-to-tensile strength ratios of the alloys vary widely (between 0.79 to 1.24 and 0.52 to 0.86, respectively). A linear dependence between shear yield strength and tensile or compressive yield strength (whichever is lower) of all the alloys is found. While the ultimate shear and tensile strengths also show a linear dependence, data obtained on the fully β alloys are distinct. Finite element analyses employing the Drucker-Prager (DP) yield condition (to account for pressure-dependence on yield), Ludwick's strain hardening model, and Rice-Tracey failure criterion were performed to gain insights into the experimental trends. Results show that TCA decreases the shear yield stress while the shear strength is sensitive to the rate of hardening. A good correlation between the experimental and simulated shear-to-tensile yield strength ratios was observed. Based on a large, simulated dataset (generated using different combinations of material parameters), an empirical relation between shear strength, TCA, and tensile strengths was identified. Graphical abstract: Image, graphical abstract